1977
DOI: 10.1002/jez.1402000310
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectricity and regeneration. I. Initiation of frog limb regeneration by minute currents

Abstract: We have applied 0.2 pamps of current to the forelimb stump of Rana adults for several weeks. The stimulator was designed to avoid introduction of any physiologically active electrode products into the tissue. Current was applied to the dorsal postaxial region of the stump. Cathodal (i.e., distally negative) current initiated partial regeneration; anodal (i.e., distally positive) current initiated extensive destruction of the limb; while implantation of sham stimulators (delivering no current) yielded limbs sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(65 citation statements)
references
References 17 publications
6
59
0
Order By: Relevance
“…It has been shown that transepithelial potential (TEP)-driven electric current densities (J I ) correlate with and are required for regeneration in amphibians (Borgens et al, 1977b;Jenkins et al, 1996;Nawata, 2001;Reid et al, 2009). Electrical stimulation induces some regeneration in non-permissive adult frog and rat limbs (Becker, 1972;Borgens et al, 1977a;Leppik et al, 2015;Smith, 1967). Moreover, engineered devices (Golding et al, 2016) partially induce mouse digit tip regeneration (Hechavarria et al, 2010) and are in clinical trials to improve paraplegia (Shapiro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that transepithelial potential (TEP)-driven electric current densities (J I ) correlate with and are required for regeneration in amphibians (Borgens et al, 1977b;Jenkins et al, 1996;Nawata, 2001;Reid et al, 2009). Electrical stimulation induces some regeneration in non-permissive adult frog and rat limbs (Becker, 1972;Borgens et al, 1977a;Leppik et al, 2015;Smith, 1967). Moreover, engineered devices (Golding et al, 2016) partially induce mouse digit tip regeneration (Hechavarria et al, 2010) and are in clinical trials to improve paraplegia (Shapiro et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated by the same authors that frog limb regeneration could be initiated by driving a small steady current through the stump. 87 The artificial current was driven by a mercury cell battery implanted in the dorsal lymph sac. Current was pulled through the tissue to the mercury cell from the end of the stump through a Ringer's solution-soaked wick (Fig.…”
Section: Sodium and Clcs In Xenopus Wound Healingmentioning
confidence: 99%
“…Such electric fields are generated when the epithelial layer is disrupted instantaneously and the lesion short-circuits the transepithelial potential difference (2)(3)(4)(5)(6)(7). Electric currents at wounds in human skin (4,(8)(9)(10)(11) and in rodent cornea and skin (5,7,(12)(13) have been measured with various techniques, such as vibrating probes, micro-glass electrodes, micro-needle arrays, and bioelectric imagers (5,12,(14)(15)(16). For example, it is reported that a large outward current of 4 mA cm -2 was measured at the wound edges of rat cornea and human skin.…”
Section: Introductionmentioning
confidence: 99%